Research priorities for drivers of food choice for food system transformation in South Asia: Proceedings of a collaborative workshop - Blake, Christine E.; Kim, Sunny S.; Frongillo, Edward A.; Menon, Purnima (Elsevier, 2025)
Agrifood systems in South Asia are highly productive, but substantial challenges including poverty, climate change, and environmental degradation complicate progress toward achieving sustainable healthy diets for all. The dynamics of food systems and the consequence of their rapid transformation for food choice behaviors that contribute to healthy and unhealthy diets are not well understood [1]. Food choice is defined as a decision-making process through which individuals and households consider, acquire, prepare, distribute, and consume foods and beverages [2,3]. Understanding drivers of food choice (DFC) is important for achieving sustainable healthy diets, but evidence is lacking. This article outlines collectively derived priorities for future research on DFC in South Asia. A collaborative workshop was convened in March 2023 in Dhaka, Bangladesh, with experts from the region. The workshop emphasized the application of a science of food choice framework to guide identification of priorities for research on DFC in South Asia. Priorities were derived through an interdisciplinary collaborative process to clarify what is known and not known about DFC in the context of Food Systems Transformation in the region with emphasis on a continuum of food choice behaviors (production, acquisition, preparation, distribution, and consumption). Workshop participants identified the following 3 main priorities for future research on DFC that address knowledge gaps that emerged from discussions: 1) intrahousehold dynamics and behaviors, 2) adolescent food choice, and 3) market and food acquisition linkages. Specific research needs to emphasize the importance of multigenerational data, food allocation, perceptions on food safety, adolescent food choice behaviors, and the need for longitudinal data on linkages between market availability and food choice behaviors. Building a body of evidence on DFC and tools for monitoring and assessing food choice behaviors is essential for designing effective policies and programs that allow all individuals to have healthy and sustainable diets in South Asia.